+0  
 
0
567
1
avatar

how to find x in the question Sinh(x-3)=1 even if i expand it into e terms i cant seem to get it

Guest Apr 23, 2015

Best Answer 

 #1
avatar+20025 
+10

How to find x in the question Sinh(x-3)=1 even if i expand it into e terms i cant seem to get it

I.

$$\small{\text{
$
\begin{array}{rcl}
\sinh{(x-3)} &=& 1 \quad | \quad \sinh^{-1} \\
x-3 &=& \sinh^{-1}(1) \\
x &=& 3 + \sinh^{-1}(1) \\
x &=& 3 + 0.88137358702\\
x &=& 3.88137358702\\
\end{array}
$
}}$$

II.

$$\boxed{
\small{\text{
$
\sinh(x)=\frac{1}{2}\cdot \left( e^x - e^{-x}\right)
\qquad \sinh(x-3)=\frac{1}{2}\cdot \left( e^{x-3} - e^{-(x-3)}\right)
$
}}}$$

$$\small{\text{$
\begin{array}{rcl}
\sinh(x-3) &=& 1\\
\frac{1}{2}\cdot \left( e^{x-3} - e^{-(x-3)}\right) &=& 1\\
e^{x-3} - e^{-(x-3)} &=& 2 \\
e^{x-3} - \frac{1}{e^{x-3}} &=& 2 \quad | \quad u = e^{x-3}\\
u-\frac{1}{u} &=& 2 \quad | \quad \cdot u\\
u^2-1 &=& 2\cdot u \\
u^2 -2\cdot u - 1 &=& 0 \\
u_{1,2} &=& \frac{ 2\pm \sqrt{4-4\cdot(-1) } }{2}\\
u_{1,2} &=& \frac{ 2\pm \sqrt{2\cdot4 } }{2}\\
u_{1,2} &=& \frac{ 2\pm 2\cdot\sqrt{ 2 } }{2}\\
u_{1,2} &=& 1\pm \sqrt{ 2 }\\
\end{array}
$}}$$

$$\small{\text{$
\begin{array}{rcll}
u &=& e^{x-3} \quad & | \quad \ln\\
\ln(u) &=& (x-3) \cdot \ln(e) \quad & | \quad \ln(e) = 1 \\
\ln(u) &=& x-3 \\
\boxed{x = 3 + \ln(u)}
\end{array}
$
}}$$

$$\small{\text{$
\begin{array}{rcl|rcl}
u_1 &=& 1+\sqrt{2} \quad & \quad u_2 &=& 1-\sqrt{2}\\
x_1 &=& 3 + \ln(u_1) \quad & \quad x_2 &=&3 + \ln(u_2) \\
x_1 &=& 3 + \ln(1+\sqrt(2)) \quad & \quad x_2 &=&3 + \ln(\underbrace{1-\sqrt(2)}_{<0\text{ no solution!}}) \\
x &=& 3 + \ln(1+\sqrt(2)) \\
x &=& 3 + \ln( 2.41421356237 ) \\
x &=& 3 + 0.88137358702\\
x &=& 3.88137358702\\
\end{array}
$
}}$$

heureka  Apr 23, 2015
 #1
avatar+20025 
+10
Best Answer

How to find x in the question Sinh(x-3)=1 even if i expand it into e terms i cant seem to get it

I.

$$\small{\text{
$
\begin{array}{rcl}
\sinh{(x-3)} &=& 1 \quad | \quad \sinh^{-1} \\
x-3 &=& \sinh^{-1}(1) \\
x &=& 3 + \sinh^{-1}(1) \\
x &=& 3 + 0.88137358702\\
x &=& 3.88137358702\\
\end{array}
$
}}$$

II.

$$\boxed{
\small{\text{
$
\sinh(x)=\frac{1}{2}\cdot \left( e^x - e^{-x}\right)
\qquad \sinh(x-3)=\frac{1}{2}\cdot \left( e^{x-3} - e^{-(x-3)}\right)
$
}}}$$

$$\small{\text{$
\begin{array}{rcl}
\sinh(x-3) &=& 1\\
\frac{1}{2}\cdot \left( e^{x-3} - e^{-(x-3)}\right) &=& 1\\
e^{x-3} - e^{-(x-3)} &=& 2 \\
e^{x-3} - \frac{1}{e^{x-3}} &=& 2 \quad | \quad u = e^{x-3}\\
u-\frac{1}{u} &=& 2 \quad | \quad \cdot u\\
u^2-1 &=& 2\cdot u \\
u^2 -2\cdot u - 1 &=& 0 \\
u_{1,2} &=& \frac{ 2\pm \sqrt{4-4\cdot(-1) } }{2}\\
u_{1,2} &=& \frac{ 2\pm \sqrt{2\cdot4 } }{2}\\
u_{1,2} &=& \frac{ 2\pm 2\cdot\sqrt{ 2 } }{2}\\
u_{1,2} &=& 1\pm \sqrt{ 2 }\\
\end{array}
$}}$$

$$\small{\text{$
\begin{array}{rcll}
u &=& e^{x-3} \quad & | \quad \ln\\
\ln(u) &=& (x-3) \cdot \ln(e) \quad & | \quad \ln(e) = 1 \\
\ln(u) &=& x-3 \\
\boxed{x = 3 + \ln(u)}
\end{array}
$
}}$$

$$\small{\text{$
\begin{array}{rcl|rcl}
u_1 &=& 1+\sqrt{2} \quad & \quad u_2 &=& 1-\sqrt{2}\\
x_1 &=& 3 + \ln(u_1) \quad & \quad x_2 &=&3 + \ln(u_2) \\
x_1 &=& 3 + \ln(1+\sqrt(2)) \quad & \quad x_2 &=&3 + \ln(\underbrace{1-\sqrt(2)}_{<0\text{ no solution!}}) \\
x &=& 3 + \ln(1+\sqrt(2)) \\
x &=& 3 + \ln( 2.41421356237 ) \\
x &=& 3 + 0.88137358702\\
x &=& 3.88137358702\\
\end{array}
$
}}$$

heureka  Apr 23, 2015

22 Online Users

avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.